Exploring diversity and biotechnological potential of lactic acid bacteria from tocosh - traditional Peruvian fermented potatoes - by high throughput sequencing (HTS) and culturing. (January 2018) - Jiménez, Eugenia; Yépez, Alba; Pérez-Cataluña, Alba; Ramos Vásquez, Elena; Zúñiga Dávila, Doris; Vignolo, Graciela; Aznar, Rosa
Abstract: Lactic acid bacteria (LAB) diversity associated with tocosh, Peruvian traditional fermented potatoes, was for the first time investigated by culturing and high throughput sequencing (HTS) approaches. They were applied on three samples i.e. freshly harvested potatoes, one-month and eight-months production. While by culture-dependent approach a few Lactobacillus (Lb) species ( Lb . sakei, Lb. casei, Lb. farciminis, Lb. brevis, Lb. fermentum ) and Leuconostoc (Ln) mesenteroides were identified, twenty-four OTUs belonging to six LAB genera were considered in tocosh samples by HTS, being Lactobacillus dominant in all three samples. LAB predominated on fresh potatoes, while Clostridium, Zymophilus and Prevotella were the most abundant genus in 1- and 8-months tocosh samples. When biotechnological features were investigated, amylase and phytate-degrading abilities as well as EPS and group B vitamin (riboflavin and folate) production were exhibited by several Lb. sakei and Ln. mesenteroides strains. Safety traits of major LAB species from tocosh showed antibacterial activities as well as biogenic amines production capacity. The molecular inventory achieved by HTS approach provided information on LAB population composition during fermentation of this ancestral potato fermented product while culturing allowed the selection of LAB strains suitable for novel functional cultures design for the production of fermented starchy products. Highlights: This is the first study on the tocosh LAB diversity. LAB populations were dominated by Lactobacillus at any stage in tocosh fermentation. Lb. sakei and Lc. mesenteroides were present in all tocosh samples. Out of twenty-four LAB species detected, six were recovered by culturing. Tocosh LAB isolates exhibited characteristics of biotechnological interest.